The Analysis of an IT Film Using Charles Sanders Pierce's Semiotic Theory - Michelle Valena Joesoef; Adrallisman Adrallisman (e-LinguaTera, 2023)
The title of this study is aimed to explore the kind of signs that represented including icons, indexes, and symbols found in the film. This research also analyzed the relationship of signs in the ‘IT’ film with representament, object, and interpretant. This research is used descriptive qualitative method. The data for this study were collected from the ‘IT’ film used note taking as its her main research instrument. The writers purposively selected a number of signs including seven icons, fifteen indexes, and five symbols. The results of the analysis revealed that icons, indexes, and symbols could indeed be interpreted using Peirce’s semiotic theory, especially the relationship between their representament, object, and interpretant. The blood on water and missing girls shoes, for example, the icon of the blood and murdered mystery; dark basement is an index of the appearance of blazing eye; and the water culvert are a symbol of the scary and mysterious place. Keywords: Theory, Semiotics, Peirce’s Descriptive Qualitative, Film.